Weihnachtsausstellung : 1994. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1994)
Annen, Giro ; Aschwanden, Edi ; Balzli, Berta ; Baumann, Marianne ; Bigler, Marc ; Böniger, Elsbeth ; Cassanello-Stauffer, Simone ; Danz, Pascal ; Ebinger, Moritz ; Feller, Beat ; Fischer, Alexander ; Fivian, Martin ; Franticek ; Frentzel, Gunter ; Gehbauer, Urs ; Haag, Filip ; Hamacher, Christiane ; Indermühle, Christian ; etc.
Weihnachtsausstellung 1994, Kunsthalle Bern, Bern, 17.12.1994 - 12.1.1995
boek